KINERJA DAN NILAI TAMBAH AGROINDUSTRI SABUT KELAPA PADA KAWASAN USAHA AGROINDUSTRI TERPADU (KUAT) DI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - Safitri, Yunica; Abidin, Zainal; Rosanti, Novi (Lampung University, 2014)
The research aims to analyze (1) the performance (physic and financially) of cocofiber agroindustry, (2) added value of coco fiber agroindustry. The research was conducted in Kawasan Usaha Agroindustri Terpadu(KUAT) at Pesisir Selatan Sub-District of Pesisir Barat District and the location was choosen purposively. Research location was chosen purposively based on the quantity of workers. Data were analyzed using descriptive quantitative method. The results showed that (1) performance of coco fiber agroindustry was profitable with amount of productivity of business agroindustry 2.50, the productivity of labor 76,56 kg/HOK and the capacity 67 %, whereas the coco fiber agroindustry financially feasible as shown with the NPV value of Rp 1,224,513.693, IRR 36.58%, Net B/C 2.77, Gross B/C 1.21 and Payback period for 5.51 years, (2) the coco fiber agroindustry gives added value of Rp 189.04/kg with the ratio 57.55%.Key words: added value, agroindustry, coco fiber, financial, performance